All Days 2000
DOI: 10.4043/12090-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Normalized Soil Parameter Procedure for Evaluating In-Situ Undrained Shear Strength

Abstract: The authors examined the results of 172 CKoU direct simple shear (DSS) tests. Their research has led to four important conclusions. Firstly, the test results confirm observations by other investigators that an acceptable correlation does not exist between the shear strength ratio, cu/?'v, and plasticity index, Ip. Secondly, consolidation pressure has a greater effect on cu/?'v than Ip and should be considered when evaluating DSS test results for use in a normalized soil parameter (NSP) procedure such as SHANSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The gradient of the soil undrained shear strength was adopted as k = 2 kPa/m in this study. Although this is a higher gradient than found in the Gulf of Mexico (Quirós et al, 2000), it is in line with other regions where suction caissons are used (Colliat et Load capacity of caisson anchors exposed to seabed trenching Feng/Gourvenec/White Ocean Engineering_accepted_Sept 2018 8 al., 2010; Erbrich and Hefer, 2002). The soil was modelled as linear elastic, perfectly plastic obeying a Tresca failure criterion.…”
Section: Materials Properties and Interface Conditionssupporting
confidence: 80%
“…The gradient of the soil undrained shear strength was adopted as k = 2 kPa/m in this study. Although this is a higher gradient than found in the Gulf of Mexico (Quirós et al, 2000), it is in line with other regions where suction caissons are used (Colliat et Load capacity of caisson anchors exposed to seabed trenching Feng/Gourvenec/White Ocean Engineering_accepted_Sept 2018 8 al., 2010; Erbrich and Hefer, 2002). The soil was modelled as linear elastic, perfectly plastic obeying a Tresca failure criterion.…”
Section: Materials Properties and Interface Conditionssupporting
confidence: 80%
“…The exponent n = 0.9 indicates a smaller effect of σ vc than for sand and silt, where n = 0.5 was found to give the best fit with the data. Quiros et al (2000) also plotted the static shear strength from normally consolidated DSS tests as a function of consolidation stress. Their data included 172 tests on clays with plasticity index between I p = 14% and 101%.…”
Section: Static Dss Strength Of Nc Claymentioning
confidence: 99%
“…Therefore, the authors do not recommend the use of c u /σ ' vc -PI correlations, particularly not Skempton's 1957 correlation 9 . Quirós et al 10 have shown that a more useful correlation exists between c u /σ ' vc and σ ' v .…”
Section: Comparison Of Stratigraphiesmentioning
confidence: 99%